Factors influencing the perception of protective isolation in patients undergoing haematopoietic stem cell transplantation: A multicentre prospective study. (20th August 2019) - Biagioli, Valentina; Piredda, Michela; Annibali, Ombretta; Tirindelli, Maria Cristina; Pignatelli, Adriana; Marchesi, Francesco; Mauroni, Maria Rita; Soave, Sonia; Del Giudice, Elisabetta; Ponticelli, Elena; Clari, Marco; Cavallero, Sandra; et al.
Abstract: Objectives: To identify which factors can influence the patients' perception of protective isolation following Haematopoietic Stem Cell Transplantation (HSCT). Methods: This is a prospective study conducted in 10 Italian centres, members of the Italian Group of stem cell transplant (GITMO). Patients' perception of protective isolation was assessed using the ISOLA scale between 7 and 9 days post‐transplant. Statistical linear regression analysis was performed. Results: The participants were 182 adult patients receiving autologous (48%) or allogeneic (52%) HSCT in protective isolation. Male sex ( β = .152), education level ( β = −.245), double room ( β = .186), satisfaction with visiting hours ( β = −.174) and emotional support from nurses ( β = −.169) were independently associated with isolation‐related suffering . Significant predictors of the relationship with oneself included body temperature ( β = −.179), fatigue ( β = −.192) and emotional support from nurses ( β = −.292). Factors independently associated with the relationship with others were education ( β = −.230), chemotherapy cycles ( β = −.218), pain ( β = .150) and satisfaction with visiting hours ( β = −.162). Conclusion: Healthcare providers should pay greater attention in caring for those patients who are at risk for a negative isolation experience. Nurses should provide emotional support.